Teacher’s Perspectives on Young Children's Computational Thinking Skills through Unplugged Coding Activities, A Case Study of Children Aged 5-6 Years - Choiriyah Choiriyah; Linda Pertiwi; Rohanah Rohanah; Elen Valencia (Indonesian Journal of Early Childhood Education Studies, 2025)
This study explores the development of computational thinking (CT) skills in early childhood through unplugged coding activities, focusing on the perspectives of teachers as observers and facilitators. Using an assessment instrument centered on four core CT components such as decomposition, algorithmic thinking, pattern recognition, and abstraction, the research was conducted with children aged 5–6 years engaging in a fruit skewer-making activity. The results demonstrate a strong alignment between assessment findings and teacher observations. Children showed progress in following procedural steps, recognizing and replicating patterns, breaking down tasks, and abstracting essential information. Teachers reported increased motivation, confidence, and problem-solving abilities among the children. These findings emphasize the importance of integrating unplugged coding into early childhood curricula and highlight the crucial role of teachers in creating supportive learning environments. The study suggests that teacher insights are essential for bridging theory and practice in CT education and recommends institutional support for resources and training to sustain effective implementation.